Analysis of the changes in the circumferences and the range of active motion of upper limbs in women after mastectomy participating in rehabilitation - Hanna Styczyńska; Katarzyna Strojek; Anna Fajto; Zuzanna Piekorz; Walery Zukow (Kazimierz Wielki University, 2016)
Nipple cancer is the most frequent women's neoplastic disease. In Poland, it is approximately 20% of malignant detected neoplasm among this group. Breast cancer is not only one of the most serious women's numerous prevalence diseases; it is also a common reason of anxiety among healthy ones. Supplementary to basic treatment of breast cancer (radiotherapy and surgery) is early and constant rehabilitation program for women after mastectomy. The aim of the study was to valuate alternations within volumes of the upper limb followed by mastectomy and their accurate analysis regarding movement range in the course of therapeutic rehabilitation. 30 women who were after breast cancer dislodging participated in the study.. The patients were treated with therapeutic rehabilitation which lasted for 6 weeks. Before and after the therapy, the women were examined. In conclusion it was found that complex rehabilitation in women, who had mastectomy, has a crucial influence on increasing movement range and reduction of lymphedema regarding the limb on the operated side.